A comparative study between Malaysia, Australia & Singapore: law protecting pedestrian / Noorshazlia Razali … [et al.] - Razali, Noorshazlia; Mohd Ridzuan, Ain Farhani; Mohd Noh, Nurfarah Syahidah; Ismail, Maizatul Izyan (2014)
This research aims at determining the necessity to improve the law protecting pedestrians in Malaysia replacing the current section 75 of the Road Transport Act 1987. The reason why the topic was chosen is because the rate of fatal accidents involving pedestrians has increased each year. There are still many Malaysians who are not aware that pedestrians are also a group that have right of way when using the road provided with pedestrian facilities. A team of four members conducted this research as part of a compulsory requirement prior to the completion of Bachelor in Legal Studies (Hons) degree in Universiti Teknologi MARA Malaysia. There are five chapters in this research that discusses and analyzes the inadequacies in the current law protecting pedestrians and the need to implement it. The chapter begins with an introduction on current situation of pedestrian in Malaysia and its regulation and proposed implementation by adopting laws from Australia and Singapore. The next chapter is on comparative studies between Malaysia, Singapore and Australia followed by a chapter on findings from the interviews held with our lecturers and students. Lastly, the conclusive chapter entails recommendations to implement law protecting pedestrians in Malaysia.